Isolation and Characterization of Cellulolytic Bacteria from Soil around Chicken Coop - Latusi Anggriani; Dewinta Nur Alvionita; Saldi Yulistian; Angger Hidayat (DIVERSITAS HAYATI, 2023)
Bacteria that utilize cellulose as a substrate and convert it into simpler compounds with the help of cellulase enzymes are known as cellulolytic bacteria. Cellulase enzymes are capable of breaking down cellulose into glucose. Cellulolytic bacteria are bacteria that can produce cellulase enzymes and are typically found in areas containing compost, soil rich in leaf litter, as well as agricultural and livestock soils. The aim of this study is to obtain bacterial isolates from soil around a chicken coop. Bacterial isolates from the soil around the chicken coop were cultured on selective CMC media. The successfully isolated bacteria were then purified to obtain single colonies. The obtained single colonies were characterized to determine the type of cellulolytic bacteria that were successfully isolated. Subsequently, testing was conducted to measure the cellulase enzyme activity produced by the obtained isolates. Four isolates of bacteria successfully grew on the selective CMC media. These four isolates were identified as gram-negative bacteria with a rod-shaped cell morphology. Enzyme activity testing was only performed on isolate LD 2, as it exhibited a clear zone indicating enzyme activity. The highest cellulase enzyme activity value was 0.0062 U/mL, with a 30-minute incubation time of the cell supernatant at 37°C, and a specific enzyme activity of 0.1891 U/mg. Based on the conducted research, only one isolate from the soil around the chicken coop exhibited enzyme activity